A Cyanotic Newborn with a Pink Right Upper Extremity - Matthias Beichl; Andreas Hanslik; Daniel Zimpfer; Judith Rittenschober-Boehm; Katrin Nagl; Ina Michel-Behnke (Case Reports in Pediatrics)
Aberrant origin of the subclavian artery (SCA) is a well-known vascular anomaly as part of congenital heart diseases with the left subclavian artery (LSCA) being more frequently affected than the right subclavian artery (RSCA). Complete isolation of the SCA is an even more infrequent aortic arch anomaly, occurring in less than 1% for the LSCA and even less for the RSCA. Isolation of the RSCA in patients with d-transposition of the great arteries (D-TGA) is even scanter with only a hand full of cases being reported in the literature. However, isolation of the RSCA has important implications on hemodynamics and surgical strategies. In this case report, we present a newborn patient with D-TGA which presented with distinct differential cyanosis. While the right upper extremity appeared pink with an oxygen saturation of 100%, the rest of the body was cyanotic. At first, this appearance was interpreted as the Harlequin phenomenon during primary care. However, detailed echocardiography revealed an aberrant origin of the RSCA from the right pulmonary artery, which led to the differential cyanosis. The patient underwent arterial switch operation on day of life two including dissection and reimplantation of the RSCA. The special hemodynamic situation of this is discussed in terms of pathophysiology and as well as its impact on perioperative and surgical management.